Effects of timing of signal indicating jump directions on knee biomechanics in jump-landing-jump tasks - Stephenson, M. L.; Hinshaw, T. J.; Wadley, H. A.; Zhu, Q.; Wilson, M. A.; Byra, M.; Dai, B. (Sports Biomechanics, 2018)
A variety of the available time to react (ATR) has been utilised to study knee biomechanics during reactive jump-landing tasks. The purpose was to quantify knee kinematics and kinetics during a jump-land-jump task of three possible directions as the ATR was reduced. Thirty-four recreational athletes performed 45 trials of a jump-land-jump task, during which the direction of the second jump (lateral, medial or vertical) was indicated before they initiated the first jump, the instant they initiated the first jump, 300 ms before landing, 150 ms before landing or at the instant of landing. Knee joint angles and moments close to the instant of landing were significantly different when the ATR was equal to or more than 300 ms before landing, but became similar when the ATR was 150 ms or 0 ms before landing. As the ATR was decreased, knee moments decreased for the medial jump direction, but increased for the lateral jump direction. When the ATR is shorter than an individual`s reaction time, the movement pattern cannot be pre-planned before landing. Knee biomechanics are dependent on the timing of the signal and the subsequent jump direction. Precise control of timing and screening athletes with low ATR are suggested.